2017
DOI: 10.3389/fimmu.2017.00820
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Regulator Deficiency Results in a Decrease in STAT1 Levels in Human Monocytes

Abstract: Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare primary immunodeficiency disorder typically caused by biallelic autoimmune regulator (AIRE) mutations that manifests with chronic mucocutaneous candidiasis (CMC) and autoimmunity. Patients with STAT1 gain-of-function (GOF) mutations also develop CMC and autoimmunity; they exhibit increased STAT1 protein levels at baseline and STAT1 phosphorylation (pSTAT1) upon interferon (IFN)-γ stimulation relative to healthy controls. AIRE int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A small proportion of APECED patients develop recurrent infections by herpetic viruses such as HSV and VZV (~15%, Lionakis, unpublished observations), without an obvious correlation between the titers or neutralizing potential of type I interferon AAbs or the levels of STAT1 . APECED patients have also sporadically been reported to develop Giardia intestinal infections, although the mechanisms for this susceptibility remain elusive …”
Section: Clinical Manifestations Of Apeced Patientsmentioning
confidence: 99%
“…A small proportion of APECED patients develop recurrent infections by herpetic viruses such as HSV and VZV (~15%, Lionakis, unpublished observations), without an obvious correlation between the titers or neutralizing potential of type I interferon AAbs or the levels of STAT1 . APECED patients have also sporadically been reported to develop Giardia intestinal infections, although the mechanisms for this susceptibility remain elusive …”
Section: Clinical Manifestations Of Apeced Patientsmentioning
confidence: 99%
“…Autoimmune regulator is essential for proper T cell development and selection in the thymus. While Dectin-1 and CARD9 are expressed in many cell types, studies have shown that AIRE is expressed in peripheral lymphoid tissues, monocytes, and dendritic cells and that it participates in extrathymic functions ( 23 , 24 , 40 ). APECED patients produce variable titers of autoantibodies against IL-17A, IL-17F, or IL-22 associated with CMC ( 17 , 18 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients are susceptible to CMC without these autoantibodies ( 18 ), suggesting that other factors may involved in CMC in these patients. AIRE deficiency has been associated with failure in building a proper immune response by monocytes ( 23 , 24 , 41 ). Recently, it has been shown that monocytes from APECED patients have a decrease in IFN-γR2 and STAT1 protein levels that are associated with lower levels of phosphorylated STAT1 molecules after IFN-γ stimulation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations